The Thermodynamics Application In Refrigerator - Fatiatun Fatiatun; Sri Jumini; Najib Al Adib; Ismi Rahayu; Maftuh Ulumudin; Mela Afiliyani; Kusnanto Mukti Wibowo (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This article describes one of the tools to apply the laws of thermodynamics in daily life in the form of a refrigerator. This article aims to explore, understand, and understand the concept of thermodynamics in refrigerators. Thermodynamics is the field of physics that studies the relationship between heat and mechanical work, temperature and heat, and the kinematics theory of gases. Applying the basic concepts of thermodynamics to machines can support and facilitate human work. Refrigerators that operate according to the Clausius statement of fact (second law of thermodynamics). Coolers use electrical energy to transfer heat from the object being cooled to the hot outside air.